THE STRATEGY OF HIGHER EDUCATION TO ENHANCING GRADUATE EMPLOYABILITY - Liu Han; Dedy Achmad Kurniady; Sururi; Asep Suryana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research aims to explore institutional strategies to enhance graduate employability and understand the dynamics of their implementation thru a multi-actor perspective in the context of higher education in China. This study uses a qualitative approach with a case study design on a public university in China, which has been anonymized. Data were collected thru in-depth interviews with program leaders, lecturers, students, and industry representatives, and were analyzed using thematic analysis. The research results show that the strategy for improving graduate employability is multidimensional, including the reorientation of industry based curricula, strengthening work-integrated learning, developing soft skills, career development services, and collaboration with industry. However, the main finding reveals that the effectiveness of these strategies is not only determined by the existence of the programs but also by the level of integration and consistency in their implementation. Moreover, differences in perceptions among actors create a policy practice gap that affects the success of the strategy. This research emphasizes that employability needs to be understood as an ecosystem-based process involving interactions between strategies, actors, and institutional contexts, thereby contributing conceptually to understanding the complexity of the relationship between higher education and the world of work.